Genetic Diversity of West African Honey Bee (Apis ‎mellifera adansonii Latreille, 1804) from Rural and Urban ‎Areas of ‎Kwara State, North-Central Nigeria - A Iyiola, Oluyinka; J Adelaja, Olukayode; D Aderemi, Rahmat; Aliu Fulani, Soliu; E Alaba, Ademola; F Adejuwon, Seun; S Yusuf, Olayinka; B Bello, Lateefat; O Oduola, Adedayo (The Iraqi Journal of Veterinary Medicine, 2023)
Over one third of the world’s crops– including fruits, vegetables, nuts, spices, and oilseed–‎require insect pollination, and human reliance on ‎pollination services by honey bees (Apis ‎mellifera) to promote these crops continues to rise due to increasing demands from growing ‎human ‎populations. Identifying the effects of urbanization on genetic diversity on this ‎pollinating insect is important in the field of bioscience. This study aimed to investigate genetic diversity of A. mellifera in Kwara State, Nigeria, using the random amplified polymorphic DNA (RAPD) marker. ‎Thirty honey bees ‎were simultaneously collected from both rural and urban regions in ‎Kwara state, Nigeria. Samples were morphologically identified using ‎standard methods, ‎genomic DNA isolated and amplified using five RAPD primers. Data collected were ‎analysed using PyElph, ‎ARLEQUIN, and GeneAlEx version 6.501 software. The results ‎showed that the DNA fragment sizes produced per primer varied from 200 to ‎‎3000 bp. Percentages of polymorphic loci amplified by each primer varied from 17.33 to 33.33%. ‎Analysis of unbiased Nei genetic ‎distance values showed that Agbede (rural) and Adewole ‎‎(urban) showed the highest value of unbiased genetic distance (0.073), while ‎Amoyo ‎‎(rural) to Idofian (urban) exhibited the lowest value (0.027). Dendrogram analysis revealed ‎genetically close relationships among the sampled ‎A. mellifera‎ populations. The low level of genetic ‎polymorphisms observed among the honey bee populations in the two ‎regions ‎indicated that there is genetic relatedness among them. This study concluded that RAPD ‎marker is a useful method for ‎understanding population genetic structure of the African honey ‎bees. These results can be used as baseline information for future genetic ‎diversity ‎assessment of honey bees in Nigeria with larger samples. It is therefore recommended that ‎there is a need to safeguard the genetic ‎diversity of A. mellifera‎ to prevent extinction or ‎gradual loss of diversity‎‎‎.